Detection of the catechol 2,3-Dioxygenase gene in three polycyclic aromatic hydrocarbon-degrading bacteria strains isolated from Khe Che, Cua Luc bay, Quang Ninh province - Phuong, La Thanh; Huu, Nguyen Ba; Cam Ha, Dang Thi (Academia Journal of Biology, 2015)
Detection of the catechol 2,3-Dioxygenase gene in three polycyclic aromatic hydrocarbon-degrading bacteria strains isolated from Khe Che, Cua Luc bay, Quang Ninh province